PENAMPILAN PERTUMBUHAN DAN PRODUKSI LIMA VARIETAS BAWANG MERAH ( Allium ascalonicum ) DI KALIMANTAN BARAT - Tietyk Kartinaty; Hartono Hartono; Serom Serom (Universitas Tribhuwana Tunggadewi, 2018)
Introduction of high yielding varieties of red onion (Allium ascalonicum) is an effort that can be done to increase red onion production in West Kalimantan. This research aims to introduce new varieties that can adaptive for the conditions of the land in West Kalimantan in order to obtain location-specific varieties as well as to accelerate the deployment of red onion Agency for Agricultural Research and Development. The research was conducted from May to July 2014 at the Visitor BPTP Plots of West Kalimantan. Research using randomized block design with four replications. The varieties used are Katumi, Bima, Mentes, Pikatan and Manjung. Variables observed included: height of plant (cm), number of tillers (clumps), number of leaves (strands), bulbs diameter (mm), weight bulbs (g), production (tons / ha). The results showed that of the five varieties of onion were tested superior results achieved ranged from 6.11 to 9.37 tons / ha. The Varieties Bima and Katumi to give the highest production of 9.37 tons / ha and 9.09 tons / ha. Both of these varieties are recommended for development in West Kalimantan.